Heat dissipation from stationary passenger car brake discs - Topouris, Stergios; Stamenković, Dragan; Olphe-Galliard, Michel; Popović, Vladimir; Tirovic, Marko (University of Ljubljana - Faculty of Mechanical Engineering, 2020)
This paper presents an experimental investigation of the heat dissipation from stationary brake discs concentrated on four disc designs: a ventilated disc with radial vanes, two types of ventilated discs with curved vanes (a non-drilled and cross-drilled disc), and a solid disc. The experiments were conducted on a purpose-built thermal spin rig and provided repeatable and accurate temperature measurement and reliable prediction of the total, convective and radiative heat dissipation coefficients. The values obtained compare favourably with computational fluid dynamics results for the ventilated disc with radial vanes and solid disc, though the differences were somewhat pronounced for the ventilated disc. The speeds of the hot air rising above the disc are under 1 m/s, hence too low to experimentally validate. However, the use of a smoke generator and suitable probe was beneficial in qualitatively validating the flow patterns for all four disc designs. Convective heat transfer coefficients increase with temperature, but the values are very low, typically between 3 W/(m2K) and 5 W/(m2K) for the disc designs and temperature range analysed. As expected, from the four designs studied, the disc with radial vanes has the highest convective heat dissipation coefficient and the solid disc the lowest, being about 30 % inferior. Convective heat dissipation coefficient for the discs with curved vanes was about 20 % lower than for the disc with radial vanes, with the cross-drilled design showing marginal improvement at higher temperatures.
Keywords: brake disc; heat dissipation; convective cooling; computational fluid dynamics; natural convection